Subject-predicate-inversion of Gender-neutral-language: An emancipatory confusion - Hermeto, João Romeiro (Journal of Gender and Power, 2020)
In this paper, I proposed a paradigm shift in Gender-Neutral-Language. The claim, which Gender-Neutral-Language can account for reality grasping and, thus, enable its actualization, is challenged; in place of an abstract reach towards social change, a more concrete emancipatory praxis must arise. Its current emancipatory prerogatives are not confronted from the standpoint of its already-established arguments but a more comprehensive standpoint of language, more specifically, of the philosophy of language.